2004
DOI: 10.2143/ac.59.2.2005166
|View full text |Cite
|
Sign up to set email alerts
|

Slow coronary flow may be a sign o diffuse atherosclerosis

Abstract: We have demonstrated the decreased FFR in the patients with SCF. Decreased FFR levels have been attributed to increased resistance in the epicardial coronary arteries due to diffuse atherosclerotic disease which has been demonstrated by IVUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
99
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 0 publications
5
99
0
4
Order By: Relevance
“…Our findings on the presence of relation between Hs-CRP and TIMI frame count, may have emerged from the contribution Hs-CRP as inflammation marker to the atherosclerotic process and related coronary flow pattern (18). Slevin et al (19) have shown the importance of CRP within the angiogenic microvessels from diseased tissues.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our findings on the presence of relation between Hs-CRP and TIMI frame count, may have emerged from the contribution Hs-CRP as inflammation marker to the atherosclerotic process and related coronary flow pattern (18). Slevin et al (19) have shown the importance of CRP within the angiogenic microvessels from diseased tissues.…”
Section: Discussionmentioning
confidence: 53%
“…Plasma concentration of interleukin-6 and CRP levels were found to be increased in patient with slow coronary flow. Pekdemir et al (18) found that the levels of CRP and TIMI frame count had no significant relationship in patients with CSFP. In this study, we assessed the levels of Hs-CRP, which is highly specific compared to CRP.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Mosseri et al (1986) suggested that occlusive disease of small coronary arteries might be etiology of SCF phenomenon. Many intravascular ultrasound studies suggested the evidence of diffuse atherosclerosis in SCF phenomenon (Cin et al 2003;Pekdemir et al 2004;Camsari et al 2008). Erdogan et al (2007) suggested that the coronary flow reserve (CFR) is impaired in patients with SCF.…”
Section: Discussionmentioning
confidence: 99%
“…12 On the other hand, intravascular ultrasonography (IVUS) studies demonstrated that increased TIMI frame count might reflect diffuse atherosclerotic involvement. 13 Hence, not only impaired function of coronary arteries but also diffuse atherosclerotic involvement of them might be the reason for the increased TIMI frame count in this population.…”
Section: Discussionmentioning
confidence: 89%